Central government and local development in Indonesia - [Tidak Terdaftar] (Oxford University Press, 1986)
Since the beginning of the New Order period in 1965 under General Soeharto, Indonesia has seen the establishment of the authority of the central government in every part of the country as well as the gradual delegation of authority to local provincial governments. This collection of essays analyzes development and change in public policy and administration during these years, and will be an invaluable resource for both development professionals and students.